Reflective Practice: Theoretical Construct or Ongoing Benefit - Yassaei, Shahla (2011)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Shahla Yassaei Entitled, "Reflective Practice: Theoretical Construct or Ongoing Benefit," January 2011. Available are both Hard and Soft Copies of the Thesis.